Protocol for the New Medicine Service study: a randomized controlled trial and economic evaluation with qualitative appraisal comparing the effectiveness and cost effectiveness of the New Medicine Service in community pharmacies in England - Boyd, Matthew; Waring, Justin; Barber, Nick; Mehta, Rajnikant; Chuter, Antony; Avery, Anthony; Salema, Nde-Eshimuni; Davies, James; Latif, Asam; Tanajewski, Lukasz; Elliott, Rachel A. (BioMed Central, 2013)
Background